Assessment of the degree of knowledge of Dentists about the use of bisphosphonates and their adverse effects: Descriptive study (Research, Society and Development, 2021)
The Dental Surgeon must be able to know the risks related to the use of bisphosphonates. This study aims to evaluate the knowledge and conduct of dental surgeons about the use of bisphosphonates and their adverse effects. The sample consisted of 60 Dental Surgeons specialized in the areas of Surgery (n = 20), Implantology (n = 20) and Periodontics (n = 20), who answered a structured questionnaire and validated by Albuquerque (2014) with 12 questions, having personal questions, topics about the anamnesis performed by these professionals and about the knowledge about bisphosphonates, including indications, adverse effects and treatments used when necessary. Of the 60 participants, 88.3% have seen patients who report the use of Bisphosphonates, however only 33.3% know the oral complications of its use. It was concluded that there were a considerable number of Dental Surgeons aware of the existence of bisphosphonates, a small portion knows about the oral complications of this medication and its form of treatment.